Historical grievances and war dynamics: Old land conflicts as a cause of current forced displacements in Colombia (2019)
We explore the role of unfairly resolved land conflicts on the long-run dynamics of Colombia¿s war. We claimed that inadequately or unfairly resolved land conflicts can explain not only the emergence of rebel groups but also their repertoires and targets of violence¿notably forced displacements. The identification strategy used combines the use of instrumental variables ¿ distance of the municipality to the railroad in 1900- with a methodology of neighbor-pair fixed effects to test the causal relation between old land conflicts and recent forced displacements. Moreover, we use mediation analysis to test the mechanisms that we hypothesize as links between the independent and dependent variables¿presence of armed groups and unfair land reform allocations. Our results show that, indeed, early 20th century land conflicts and recent forced displacements are causally linked, and their connection is mainly produced through the mediation of unfair land reform allocations and the presence of violent armed groups. We argue that unfair land reforms harbor the formation of peasant-based rebel groups and such groups promote displacements in the very same places that experienced old land conflict.